2015
DOI: 10.1007/s00438-015-1042-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, structural analysis, and expression characteristics of the maize TIFY gene family

Abstract: TIFY, previously known as ZIM, comprises a plant-specific family annotated as transcription factors that might play important roles in stress response. Despite TIFY proteins have been reported in Arabidopsis and rice, a comprehensive and systematic survey of ZmTIFY genes has not yet been conducted. To investigate the functions of ZmTIFY genes in this family, we isolated and characterized 30 ZmTIFY (1 TIFY, 3 ZML, and 26 JAZ) genes in an analysis of the maize (Zea mays L.) genome in this study. The 30 ZmTIFY ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 34 publications
(46 reference statements)
3
46
0
Order By: Relevance
“…22 Zhang et al isolated and characterized 30 ZmTIFYs and concluded that they had tissue-specific expression patterns in various developmental stages and in response to biotic and abiotic stresses. 23 Here, we identified two TIFY genes whose expressions were up-regulated by 293.7-and 144.8-fold in teosinte plants that were involved in the armyworm attacking response.…”
Section: Transcription Factormentioning
confidence: 93%
“…22 Zhang et al isolated and characterized 30 ZmTIFYs and concluded that they had tissue-specific expression patterns in various developmental stages and in response to biotic and abiotic stresses. 23 Here, we identified two TIFY genes whose expressions were up-regulated by 293.7-and 144.8-fold in teosinte plants that were involved in the armyworm attacking response.…”
Section: Transcription Factormentioning
confidence: 93%
“…10C; Table II). The Tify transcription factor family has been connected to a variety of abiotic and biotic stresses and also to development (Zhang et al, 2015). In maize (Zea mays), ZML2, a Tify family member, and MYB11 together repress COMT expression (VĂ©lez-BermĂșdez et al, 2015).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…The TIFY gene family is specific to land plants and was first found in Arabidopsis and annotated as a transcription factor [1,2]. This gene family contains a core motif, TIF[F/Y]XG, previously known as ZIM (a zinc-finger protein expressed in inflorescence meristem) [1], and includes 20 members in Rice, 18 members in Arabidopsis, and 27 members in Maize [3][4][5]. Depending on the conservative domain, the proteins are divided into two groups: Group I containing the C2C2-GATA (CX2CX20CX2C) conservative domain, which is absent in Group II.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, AtPPD2 interacts with AtLHP1 to directly or indirectly regulate several target genes to affect lateral organ development, while Arabidopsis ppd2 shows greater leaf breadth than wild-type (WT) [17]. In Maize, ZmTIFY4, 5, 8, 26, and 28 respond to drought; additionally, ZmTIFY1 19 and 28 show upregulation when treated by three kinds of pathogens [5]. In summary, different TIFY subfamily members have different functions during plant growth and development, as well as different responses to phytohormone treatment and abiotic stress.Populus trichocarpa serves as a model forest species and is widely used in forest tree genomics studies [18].…”
mentioning
confidence: 99%